Comparison of the neurobiological effects of attribution retraining group therapy with those of selective serotonin reuptake inhibitors - Wang,C. (2013)
The aim of this study was to compare the effectiveness of attribution retraining group therapy (ARGT) with selective serotonin reuptake inhibitors (SSRIs) in the treatment of major depressive disorder (MDD), generalized anxiety disorder (GAD), and obsessive-compulsive disorder (OCD). Subjects were sequentially recruited and randomized into two groups, one receiving ARGT (n = 63) and the other SSRIs (n = 66) for 8 weeks. Fifty-four ARGT outpatients with MDD (n = 19), GAD (n = 19), and OCD (n = 16) and 55 SSRI outpatients with MDD (n = 19), GAD (n = 19), and OCD (n = 17) completed the study. All subjects were assessed using the Hamilton Depression Scale and Hamilton Anxiety Scale before and after treatment. The 10-item Yale-Brown Obsessive Compulsive Scale was employed only for OCD subjects. Plasma levels of serotonin, norepinephrine, cortisol, and adrenocorticotropic hormone were also measured at baseline and 8 weeks after completion of treatment. Symptom scores were significantly reduced (P < 0.001) in both the ARGT and SSRI groups at the end of treatment. However, MDD, GAD and OCD patients in the ARGT group had significantly lower plasma cortisol concentrations compared to baseline (P < 0.05), whereas MDD and OCD patients receiving SSRIs showed significantly increased plasma levels of serotonin (P < 0.05). These findings suggest that ARGT may modulate plasma cortisol levels and affect the hypothalamus-pituitary-adrenal axis as opposed to SSRIs, which may up-regulate plasma serotonin levels via a different pathway to produce an overall improvement in the clinical condition of the patients.